Pengaruh Kualitas Pelayanan terhadap Keputusan Konsumen Dalam Menggunakkan Jasa pada PT BCA - Acep Samsudin; Rusdi Hidayat; Kinanti Sekar Kirana; lvira Aprilia Primastika; Alvianti Notia Pramesti; Dela Kristiana; Priscilia Salsabilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine the effect of Quality of Service Characteristics on Customer Satisfaction in the PT. Bank Central Asia (BCA). The analytical technique used is to collect data sources that are used as objects. The results of the study indicate that the quality of service simultaneously affects customer satisfaction in PT. Bank Central Asia (BCA). The quality of services that include variables Responsiveness, Empathy, Assurance, and Reliability in a partial effect on customer satisfaction in PT. Bank Central Asia (BCA). Keywords: Responsiveness, Empathy, Assurance, Reliability and customer satisfaction